Antibiotic resistance profiles of enterobacteria isolated from weaned piglets - Barroso, Marlon do Valle (Universidade Federal de Viçosa, 2019)
Pork meat is the most consumed source of animal protein in the world. In order to achieve this high productive efficiency, swine farming has undergone improvements in several sectors. Among these, the supply of antibiotics to improve animal performance and efficiency has been widely discussed, mainly due to the emergence of multiresistant bacteria. This study aimed to evaluate the susceptibility profile of Enterobacteriaceae isolated from feces of weaned piglets and to investigate the distribution of resistance genes and plasmids in the multiresistant isolates. A total of 618 isolates of the Enterobacteriaceae family were obtained from fecal samples fed a control diet without antibiotics (n = 384) or diet containing colistin and tylosin (n = 234). The susceptibility of the isolates against 12 antibiotics was evaluated using the breakpoint technique. From the isolates obtained, 54% (n = 334) showed resistance to at least four antibiotics and were defined as multiresistant. The highest frequencies of resistance were observed for the antibiotics tetracycline (81%), ampicillin (90%) and amoxicillin (85%). Significant differences in the frequency of colistin (P<0.001), cephalexin (P<0.001), kanamycin (P<0.026) and doxycycline (P<0.001) resistance were observed among the bacterial isolates obtained from treatment control + antibiotics when compared to the control. The isolates were grouped based on genotypic fingerprinting (BOX-PCR) and ninety-four isolates with greater number of resistance phenotypes had the 16S rRNA gene sequenced and the distribution of resistance genes assessed by multiplex PCR. Results indicated a close association between the presence of the resistance genes and the resistance phenotype observed in vitro. At least one gene for the extended-spectrum β-lactamases (bla TEM , bla SHV or bla CTX - M ) was found in all genera of enterobacteria analyzed. In addition, it was demonstrated the transfer, through conjugation, of the mcr-1 gene from the isolate Escherichia coli UFV-627 to the E. coli K12 (Nal R , F - ) recipient strain. These results indicate a high frequency of antibiotic resistance among bacterial isolates obtained from feces of weaned piglets that received rations with or without antibiotics, which corroborates the hypothesis that the gastrointestinal tract of piglets represents a potential reservoir of multiresistant enterobacteria. In addition, the results suggest that horizontal transfer mechanisms, such as conjugation and ICEs, between phylogenetically related species, may mediate the spread of these resistance genes in the gastrointestinal tract of these animals. Keywords: Enterobacteria. Antibiotic resistance. Weaned piglets. ESBL genes. mcr-1 and conjugative plasmids

A carne de origem suína é a fonte de proteína animal mais consumida no mundo. Para alcançar essa alta eficiência produtiva, as suinoculturas passaram por melhorias em diversos setores. Dentre essas, o fornecimento de antibióticos para melhorar o desempenho e eficiência animal vem sendo amplamente discutido, principalmente pelo surgimento de bactérias multirresistentes. Os objetivos deste estudo foram avaliar o perfil de susceptibilidade a antibióticos de enterobactérias isoladas de fezes de leitões desmamados e investigar a distribuição de genes de resistência e de plasmídeos nos isolados multirresistentes obtidos. Um total de 618 isolados da família Enterobacteriaceae foram obtidos a partir das fezes de leitões alimentados com ração controle sem antibióticos, (n=384) ou com ração contendo os antibióticos colistina e tilosina (n=234). A susceptibilidade dos isolados foi investigada contra 12 antibióticos por meio da técnica do breakpoint. Dos isolados obtidos, 54% (n=334) apresentaram resistência a pelo menos quatro antibióticos e foram definidos como multirresistentes. As maiores frequências de resistência foram observadas param os antibióticos tetraciclina (81%), ampicilina (90%) e amoxicilina (85%). Diferenças significativas no perfil de resistência para colistina (P<0.001), cefalexina (P<0.001), canamicina (P<0.026) e doxiciclina (P<0.001) foram observadas entre os isolados bacterianos obtidos do tratamento controle em relação ao tratamento controle + antibióticos. Os isolados foram agrupados com base no fingerprinting genotípico (BOX-PCR) e noventa e quatro isolados com maior número de fenótipos de resistência tiveram o gene do rRNA 16S sequenciado e a distribuição de genes de resistência foi avaliada por PCR multiplex. Foi observado relação estrita entre a presença dos genes de resistência com o fenótipo de resistência observado in vitro. Pelo menos um gene que codifica β-lactamases de espectro-estendido (bla-TEM, bla-SHV ou bla-CTX-M) foi encontrado em todos os gêneros de enterobactérias analisadas. Além disso, foi demonstrado a transferência, por meio de conjugação, do gene mcr-1 do isolado Escherichia coli UFV-627 para a linhagem receptora E. coli K 12 (Nal R , F - ), indicando a possibilidade de transferência horizontal de genes. Os resultados deste estudo indicam alta frequência de resistência a antibióticos em isolados bacterianos obtidos das fezes de leitões desmamados que receberam ração contendo ou não antibióticos, o que corrobora com a hipótese de que o trato gastrointestinal de leitões representa um reservatório potencial de enterobactérias multirresistentes. Além disso, os resultados sugerem que mecanismos de transferência horizontal, tais como plasmídeos conjugativos ou ICEs, entre espécies filogeneticamente relacionadas, podem mediar a disseminação desses genes de resistência no trato gastrointestinal desses animais. Palavras-chave: Enterobacteria. Resistência à antibióticos. Leitões desmamados. Genes ESBL, mcr-1. Plasmídeos conjugativos
Perfis de resistência a antibióticos de enterobactérias isoladas de leitões desmamados
Keywords: Enterobactérias; Antibióticos; Suínos; Microbiologia Agrícola